1987
DOI: 10.1177/000456328702400505
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Haemoglobin Analyses—Assessment of within- and between-Laboratory Performance in a Large UK Region

Abstract: SUMMARY. The performance of glycated haemoglobin methods has been assessed in 20 laboratories. The methods used in these laboratories were affinity chromatography, electroendosmosis and ion-exchange chromatography. Assessment was based on the results returned by the participating laboratories on distributed specimens. Each method displayed acceptable precision and good linearity. Overall there were substantial differences in results reported by different laboratories, though within each method group these diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 12 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…The results obtained in the present study are similar to those found in other surveys of GHb (9,10,13). A survey of the American College of Pathologists in 1990 reported interlaboratory CV that ranged from 3.4% for HPLC to 17.2% for one type of HbA x assay by ion exchange chromatography (10).…”
Section: Conclusion-supporting
confidence: 89%
See 1 more Smart Citation
“…The results obtained in the present study are similar to those found in other surveys of GHb (9,10,13). A survey of the American College of Pathologists in 1990 reported interlaboratory CV that ranged from 3.4% for HPLC to 17.2% for one type of HbA x assay by ion exchange chromatography (10).…”
Section: Conclusion-supporting
confidence: 89%
“…A survey of the American College of Pathologists in 1990 reported interlaboratory CV that ranged from 3.4% for HPLC to 17.2% for one type of HbA x assay by ion exchange chromatography (10). Similarly, in the U.K. interlaboratory CV for GHb varied between 11.2-20.1% (13). The acknowledged differences in results obtained by different methods and in different laboratories using the same method have led to the adoption of various strategies to address this problem.…”
Section: Conclusion-mentioning
confidence: 99%
“…At the time of the start of DCCT and UKPDS trials no reference material was available and as a consequence, the inter-laboratory CV was high (>20%) (49,50). The variability in results between different HbA1c methods and the multiple ways in which results were reported (e.g.…”
Section: The History Of Standardisation Of Hba1cmentioning
confidence: 99%
“…33,34 The disparate results obtained were because of the range of methods being used by laboratories, the lack of standardization, and lack of a primary reference material. Although the new generation of HbA 1c methods now demonstrate a degree of precision that could not be imagined 30 years ago, comparison of results from different laboratories would remain, at best, difficult -or, more likely, impossible -if not for standardization schemes.…”
Section: Standardization Of Hba 1c Analysismentioning
confidence: 99%